STUDI KANDUNGAN LOGAM BERAT BESI (Fe) DALAM AIR, SEDIMEN DAN JARINGAN LUNAK KERANG DARAH (Anadara granosa Linn) DI SUNGAI MOROSARI DAN SUNGAI GONJOL KECAMATAN SAYUNG, KABUPATEN DEMAK - Firmansyaf, Dhimas; Yulianto, Bambang; Sedjati, Sri (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
This study aimed to determine: Fe metal content and Fe pollution levels in water, sediment, and blood cockle (Anadara granosa) in Morosari River and Gonjol River, and coastal adjacent, Prefecture Sayung, Demak Regency. Sampling was carried out based on different time periods or seasons, i.e. July 2010 and November 2011. The research method applied was the case study method. While the selection of sampling locations, using the method of judgment (purposive sampling method). Heavy metal analysis performed using Atomic Absorbtion Spectrophotometry (AAS). The results of Fe metal content in the water showed, in July 2010: the highest at Station A4 = 25.29 mg/l and the lowest at Station B2 = 1.35 mg/l; in November 2011: the highest at Station A3 = 3.23 mg/l and the lowest at Station A2 = 0.42 mg/l. Fe metal content in the sediment, in July 2010: the highest at station B6 = 32477.34 mg/kg and the lowest at Station B1 = 14017.14 mg/kg, while in November 2011: the highest at Station A5 = 68065.87 mg/kg and lowest at Station B1 = 33667.39 mg/kg. Fe metal contents in soft tissue blood clam (Anadara granosa) in July 2010: the highest at station B5 = 2068.22 mg/kg, while in November 2011: the highest value found in the A4 station at 8.25 mg/kg.